Physicochemical and mechanical properties of cassava starch films containing honey and glycerol as co-plasticisers - Fernández, Nancy Lidia (2025)
Starch edible films are innovative, biodegradable alternatives to traditional plastic films, which can also incorporate active ingredients, providing additional functionalities. This study aimed to create various cassava starch films with different properties by using different ratios of glycerol/honey as plasticisers. Honey improved the flow of the film-forming suspensions. Water vapour permeability and moisture content of films decreased and polyphenol content increased with honey content. Films with honey were more resistant to mechanical stress (tensile strength: 9.41–20.35MPa, elastic module: 2.75–6.87MPa), but with less extensibility (elongation at break: 37.37– 23.25%). This ingredient also made the microstructure of films rougher, as observed by scanning electron microscopy and confirmed by texture image analysis. The high honey content films showed a faster and higher (80% at 100 days) degradation in vegetable compost, which promotes the potential use of this ingredient in eco-friendly food packaging applications with added health benefits.